An oleuropein-based dietary supplement may improve joint functional capacity in older people with high knee joint pain: findings from a multicentre-RCT and post hoc analysis. (January 2022) - Horcajada, Marie-Noëlle; Beaumont, Maurice; Sauvageot, Nicolas; Poquet, Laure; Saboundjian, Madleen; Costes, Berenice; Verdonk, Peter; Brands, Geoffrey; Brasseur, Jean; Urbin-Choffray, Didier; Vandenberghe, Marc; Brabants, Karl; et al.
Objectives: To investigate a 6-month intervention with an olive leaf extract (OLE) on knee functionality and biomarkers of bone/cartilage metabolism and inflammation. Design: This randomized, double-blind, placebo-controlled, multi-centric trial included 124 subjects with knee pain or mobility issues. Subjects received twice a day one capsule of placebo or 125 mg OLE (Bonolive ™, an OLE containing 50 mg of oleuropein) for 6 months. The co-primary endpoints were Knee injury and Osteoarthritis Outcome Score (KOOS) and serum Coll2-1NO2. The secondary endpoints were the subscales of the KOOS, knee pain VAS at rest and at walking, OARSI core set of performance-based tests and multiple inflammatory and bone or cartilage remodeling serum biomarkers and concentration of oleuropein's metabolites in urine. Results: At 6 months, OLE group was not efficient on global KOOS score, changes of inflammatory and cartilage remodeling biomarkers compared to placebo. Post hoc analyses demonstrated a large and significant treatment effect of OLE in a sub-group of subjects with high walking pain at baseline ( p  = 0.03). This was observed at 6 months for the global KOOS score, and each different subscale and for pain at walking ( p  = 0.02). OLE treatment was well tolerated. Conclusion: OLE was not effective on joint discomfort excepted in a sub-group of subjects with high pain at treatment initiation. As oleuropein is well tolerated, OLE can be used to relieve knee joint pain and enhance mobility in subjects with articular pain.